Children of the stone : the power of music in a hard land - Tolan, Sandy (Bloomsbury, 2015)
"Ramzi Hussein Aburedwan, a child from a Palestinian refugee camp, confronts an occupying army, gets an education, masters an instrument, dreams of something much bigger than himself, and then, through his charisma and persistence, inspires scores of others to work with him to make that dream real. The dream: a school to transform the lives of thousands of children-- as Ramzi's life was transformed-- through music"--Amazon.com.